Analysis of Road User Satisfaction Passing Through The West Boulevard Highway and The Kelapa Gading - Pulo Gebang Toll Road - Lisa Andhika Putri; Darmawan Pontan; Parwadi Moengin; Inavonna Inavonna (Green Publisher Indonesia, 2025)
This study aims to analyze the satisfaction level of road users on Jalan Boulevard Barat Raya and the Kelapa Gading - Pulo Gebang Toll Road. Evaluating user satisfaction is crucial for assessing transportation infrastructure performance and prioritizing road maintenance and development. Using a quantitative approach, data was collected through questionnaires distributed to drivers and passengers of private and online four-wheeled vehicles. The research applied the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods, focusing on nine indicators from the Indonesian Ministerial Regulation No. 14 of 2017, including requirements, procedures, completion time, costs, service specifications, implementer competence, behavior, complaint handling, and facilities. The CSI results revealed that road users are